Peculiarities of ecologically oriented recreational complexes of Europe - Levytska, Olena Hryhoriivna (Національний технічний університет "Харківський політехнічний інститут", 2024)
The demand for safe recreation conditions is growing every day. Therefore, hotels, lodges which acquire ecological characteristics, improving the interiors of the premises, the exterior of the territories, causing green areas and growing organic products, supporting the ideas of resource conservation and remediation of territories. The purpose of this article is to evaluate the most successful tourism eco-projects in Europe, to identify environmental criteria that attract vacationers and improve the quality of the environment, to evaluate the service, natural attraction and creativity of holiday destinations, to make a comparative description of hotels and resorts located in different natural areas. Service, proximity to nature and the satisfaction of visitors with interaction of nature, design of the exterior and interior, the availability of exclusive decor items, and non-standard leisure activities are the three important criteria for choosing a hotel or resort today. These three criteria were studied by the method of manual analysis of visitor reviews. Most often vacationers mention natural beauty, somewhat less often – service, and quite rarely – creativity in the design and organization of recreation. For the first time, the most successfully functioning ecological resorts in Europe are divided into groups by location and natural resources. The requirements for resorts that are popular among the visitors have been formed. The criteria of service, natural advantages and creativity in different groups are compared.

Попит на безпечні умови відпочинку зростає з кожним днем. Тому готелі, лоджі набувають екологічних характеристик, покращуючи інтер'єри приміщень, екстер'єр, озеленюючи території та вирощуючи органічну продукцію, підтримуючи ідеї ресурсозбереження та оздоровлення територій. Мета цієї статті - оцінити найбільш успішні туристичні екопроєкти в Європі, виявити екологічні критерії, що приваблюють відпочиваючих, та покращити якість довкілля, оцінити сервіс, природну привабливість та креативність місць відпочинку, провести порівняльний аналіз готелів та санаторіїв, розташованих у різних природних зонах. Сервіс, близькість до природи та задоволеність відвідувачів взаємодією з природою, дизайном екстер'єру та інтер'єру, наявністю ексклюзивних предметів декору, нестандартністю дозвілля – три важливі критерії вибору готелю чи курорту сьогодні. Ці три критерії було вивчено методом неавтоматизованого аналізу відгуків відвідувачів. Найчастіше відпочиваючі відзначають природну красу, трохи рідше – сервіс і дуже рідко – креативність у дизайні та організації відпочинку. Вперше найбільш успішно функціонуючі екологічні курорти Європи поділені на групи за розташуванням та природними ресурсами. Сформовано вимоги до курортів, які користуються популярністю у туристів. Порівнюються критерії сервісу, природних переваг та креативності у різних групах.
Особливості екологічно орієнтованих рекреаційних комплексів Європи
Keywords: wood; organic; natural landscape; деревина; органіка; природний ландшафт